2017
DOI: 10.1002/slct.201701952
|View full text |Cite
|
Sign up to set email alerts
|

Role of Specific N-Containing Active Sites in Interconnected Graphene Quantum Dots for the Enhanced Electrocatalytic Activity towards Oxygen Evolution Reaction

Abstract: Electrochemical water oxidation is a dynamic and basal approach for several energy conversion technologies such as solar fuels and metal–air batteries. Herein, we report a novel ‘nitrogen’ (N) enriched interconnected graphene quantum dots (C‐GQDs) as efficient oxygen evolution electrocatalyst, a potential candidate to replace the noble metal OER electrocatalysts. Interestingly, C‐GQDs deliver a current density of 10 mAcm‐2 at 350 mV, a small Tafel slope of 55 mV/dec and outstanding durability which is much sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…N‐CQDs are efficient oxygen evolution electrocatalyst owning to the interconnection and N‐surface functionalization . Besides, CQDs based nanocomposites, such as Co 3 O 4 /N‐CQDs, CoP/CQDs, NiCo 2 P 2 /CQDs, MnO 2 /CQDs and CoFe/CQDs can also improve the OER performance. HER, as one of half reactions of electrocatalytic water splitting, is one of the most efficient ways to produce clean fuel (hydrogen) from water.…”
Section: Applications Of Cqds In Ecmentioning
confidence: 99%
“…N‐CQDs are efficient oxygen evolution electrocatalyst owning to the interconnection and N‐surface functionalization . Besides, CQDs based nanocomposites, such as Co 3 O 4 /N‐CQDs, CoP/CQDs, NiCo 2 P 2 /CQDs, MnO 2 /CQDs and CoFe/CQDs can also improve the OER performance. HER, as one of half reactions of electrocatalytic water splitting, is one of the most efficient ways to produce clean fuel (hydrogen) from water.…”
Section: Applications Of Cqds In Ecmentioning
confidence: 99%
“…The coexistence of pyridine N and pyridine N-oxide N causes charge redistribution through π-π delocalization and reduces the *OOH thermodynamic energy barrier. [136] In addition to single N-doping, Shin et al developed a metalfree porous graphene frame which embedded N, S co-doped CDs as a dual-functional oxygen electrocatalyst for metal-air batteries. The synergistic effect of double N and S doping reduces the activation barrier of oxygen adsorption on CDs, providing numerous N and S defect sites as electrocatalytic active centers, and meanwhile the graphene synergistically enhanced the conductivity.…”
Section: Heteroatom-doped Cdsmentioning
confidence: 99%
“…After the fabrication process, TA-metal complex film composites were considered as the new-type OER active electrocatalysts [ 18 ]. Interestingly, a nitrogen-enriched graphene quantum dots (C-GQDs) catalyst was developed with an efficient electrocatalytic activity, and the charge distribution of pyridine and pyridine N-oxide is induced through the π–π delocalization process, which could encourage their OER activity [ 19 ]. Surendran et al [ 20 ] hydrothermally synthesized the spherically nanostructured carbon-enriched cobalt phosphide multi-functional electrode for water electrolyzer studies, and reported the current density of 10 mA cm −2 @ 1.63 V. Qian et al [ 21 ] prepared a cost-effective, larger specific surface area with high electrically conductive natured MWCNTs for the making of a thermo-electrochemical (TEC) catalyst by the electrochemical deposition (EPD) method.…”
Section: Introductionmentioning
confidence: 99%